Local indices within a mathematical framework for urban water distribution systems. Issue 1 (1st January 2019) - Caldarola, Fabio; Maiolo, Mario
Abstract: In this paper, a set of local energetic indices for an urban water distribution system is proposed, together with a mathematical organization of the matter which is also able to incorporate many of the well known (global) indicators. In fact, arranged such incoming indices in vectors and drawing on some notions of linear algebra and vector calculus, they are placed at the starting point of a mathematical framework that seems never used before for engineering-hydraulic purposes. It is then told how such a study and local treatment of a water network can be very useful, accurate and rich in information, and can be considered as a natural and simple theoretical development of a common global vision generally pursued so far: in particular, it is shown how it is possible to recover from the drawn layout, through suitable formulas, some of the most known and mainly used energetic parameters in a very clear and effective way.